Ecophilosophy as a Way of Life - Mathews, Freya (The Trumpeter)

(untitled) (Athabasca University Press, 2023)
The contemporary figure of the ecophilosopher perhaps holds the seeds of something that transcends philosophy in its current strictly academic, professionalized, indeed corporatized mode. This is a "something" that could, on the one hand, tie philosophy back to its own ancient, life-giving, but now lost, root in the Graeco-Roman world, and on the other hand, open it up to people searching outside the academy for a shared and reflective way of life that is authentically Earth-aligned. By means of a detailed comparison of ecophilosophy with the ancient schools of Stoicism and Epicureanism, understood not merely as intellectual discourses but as "ways of life" (Pierre Hadot), I argue that the figure of the ecophilosopher potentially offers to thoughtful people everywhere a radical pathway through the illusions of our current period of decline-and-fall towards a more adaptive life grounded in "direct, unmediated contact with the real."